MENELISIK LOGOSENTRISME PEMIKIRAN ISLAM (Tinjauan Terhadap Kritik Muhammad Arkoun) - Syafrinal randa; Haniftul Aini; Riko Putra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This paper examines Islamic thought and Arkoun's critique of the construction of Islamic thought by actualizing existing realities. The research method in this paper is exploratory descriptive research, this study aims to describe or describe the problem under study. While the exploratory method serves to deepen the study in a problem that is being studied. Arkoun as one of the Islamic thinkers who originated from al Jazair but was strongly influenced by French thought, by collaborating with new ideas in unraveling logocentrism in Islamic thought, especially in the stagnation and stagnation of Islamic thought and epistemology which is considered final. By looking at Arkoun's various criticisms of logocentrism and epistemology. Arkoun considered that there are many layers that have covered Islamic thought so that it does not see the development of science that occurs and Islamic thought which only focuses on some studies such as theology, Sufism and fiqh, does not see the development of reality. Therefore, it is necessary to re-examine or transform thinking by looking at reality and the development of epistemology by looking at relity.